HUBUNGAN ANTARA SIKAP TERHADAP KESELAMATAN KERJA DENGAN KOMITMEN ORGANISASI PADA PEGAWAI PT. PLN (PERSERO) AREA PELAKSANA PEMELIHARAAN SEMARANG - Indri Murti Astuti; Harlina Nurtjahjanti (Faculty of Psychology, Diponegoro University, 2017)
This study aims to determine the correlation between attitudes towards work safety and organizational commitment to employees of PT. PLN (Persero) Area Pelaksana Pemeliharaan Semarang. The population in this study amounted to 156 employees of PT. PLN (Persero) Area Pelaksana Pemeliharaan Semarang. The sample of the research was 70 employees obtained with incidental sampling. Measuring tool used is Attitude to Work Safety Scale (33 aitem, α = 0,958) and Organizational Commitment Scale (32 items, α = 0,934). The method of analysis used in this research is simple regression analysis. The result of this study showed a positive and significant relationship between attitudes toward work safety with organizational commitment (rxy = 0,775, p <0,001), meaning that the more positive attitude toward work safety, the higher the organization's commitment to the employees. Attitudes towards work safety contributed effectively to 60.1% of organizational commitment, while 39.9% influenced by other factors not examined in this study.